Human rights in Bangladesh : a study of standards & practices. - Bangladesh Institute of Law and International Affairs; Ford Foundation (Dhaka : Bangladesh Institute of Law and International Affairs, 2001)
Contributed articles.
"The present publication is the outcome of a research study sponsored by Ford Foundation"--T.p. verso.
Includes bibliographical references.
Keywords: Human rights -- Bangladesh